Prospects of Legal Regulation of Extradition of Persons for Criminal Prosecution or Execution of a Sentence in the Context of the Expansion of BRICS - A. Volevodz; V. Karpovich (BRICS Law Journal)
This article presents the results of a systematic analysis of the legal regulation of extradition of persons for criminal prosecution or execution of a sentence in the BRICS (BRICS+) countries. The central authorities of the BRICS (BRICS+) countries responsible for extradition are specified. The key projects of experts and initiatives undertaken by the states at the relevant BRICS platforms are studied and presented, such as the BRICS Anti-Corruption Working Group (ACWG), the BRICS Council on AntiMoney Laundering and Countering Financing of Terrorism (AML/CFT) and the BRICS Counter-Terrorism Working Group (CTWG). Taking into account the expansion of the BRICS group and the effective cooperation between the competent authorities of the BRICS countries in the sphere of international legal cooperation, the directions and possible ways for the further development of the legal regulation of extradition within the framework of the BRICS are described.